2013
DOI: 10.1108/ijcst-01-2012-0031
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of needle penetration force in denim fabric

Abstract: Purpose -This paper aims to predict the needle penetration force (NPF) in denim fabrics using the artificial neural network (ANN) and multiple linear regression (MLR) models based on the effects of various sewing parameters. Design/methodology/approach -In order to design the ANN and MLR models, four parameters including fabric weight, number of fabric layers, weave pattern, and sewing needle size are taken into account as the input parameters and NPF as the output parameter. According to these parameters, 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Generally, adding 1-5% of Lycra with cotton will stretch the fabric over the body providing a more comfortable fit. For example, Rahman [26] studied the effect of spandex ratio on fabric physical and mechanical properties such as: breaking strength, breaking extension, shrinkage and fabric growth [27][28][29][30]. The findings of this study revealed that the ratio of Lycra had a significant influence on the physical properties of woven denim fabrics.…”
Section: Introductionmentioning
confidence: 85%
“…Generally, adding 1-5% of Lycra with cotton will stretch the fabric over the body providing a more comfortable fit. For example, Rahman [26] studied the effect of spandex ratio on fabric physical and mechanical properties such as: breaking strength, breaking extension, shrinkage and fabric growth [27][28][29][30]. The findings of this study revealed that the ratio of Lycra had a significant influence on the physical properties of woven denim fabrics.…”
Section: Introductionmentioning
confidence: 85%
“…21 In textiles, the ANN method is used as an embedded-expert system in the manufacturing processes as well as used in developing a model and predicting properties of the textile materials. 22,23 Some studies 24,25 have been conducted with the help of ANN, Linear Regression, and Taguchi methodologies to predict the strength of woven fabrics. But they are only for fabrics, not for any kind of seams.…”
Section: Introductionmentioning
confidence: 99%
“…High NPF and the use of an unsuitable needle may cause fabric damages that are not noticeable during sewing on the garment but may occur after the garment has been worn for a certain period. Therefore, NPF helps to determine the damage that may occur in the sewing process [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%